2022
DOI: 10.1177/03000605221094531
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of respiratory failure after thoracic surgery: a retrospective cohort study with comparison between lobar and sub-lobar resection

Abstract: Objective Only approximately 15% of patients with lung cancer are suitable for surgery and clinical postoperative outcomes vary. The aim of this study was to investigate variables associated with post-surgery respiratory failure in this patient cohort. Methods Patients who underwent surgery for lung cancer were retrospectively studied for respiratory function. All patients had undergone lung resection by a mini-thoracotomy approach. The study population was divided into two subgroups for comparison: lobectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…In addition, the presence of emphysema and conventional static lung hyperinflation parameters, such as the percentage of low attenuation area less than −950 HU, was also demonstrated to be associated with an increased risk of postoperative respiratory failure in cases with lung cancer. 24 This study also demonstrated that pleural movement in the dependent aspect was larger than in the non-dependent aspect, even in smokers without airflow limitation compared with non-smokers (Figures 6 and 7) (Videos S2 and S3). Furthermore, MPMV ND/D decreased as MLD at maximum as inspiration increased; in other words, the extent/degree of lung parenchymal collapse at peak inspiration became larger in smokers, especially for the dependent lung field.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, the presence of emphysema and conventional static lung hyperinflation parameters, such as the percentage of low attenuation area less than −950 HU, was also demonstrated to be associated with an increased risk of postoperative respiratory failure in cases with lung cancer. 24 This study also demonstrated that pleural movement in the dependent aspect was larger than in the non-dependent aspect, even in smokers without airflow limitation compared with non-smokers (Figures 6 and 7) (Videos S2 and S3). Furthermore, MPMV ND/D decreased as MLD at maximum as inspiration increased; in other words, the extent/degree of lung parenchymal collapse at peak inspiration became larger in smokers, especially for the dependent lung field.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, the presence of emphysema and conventional static lung hyperinflation parameters, such as the percentage of low attenuation area less than −950 HU, was also demonstrated to be associated with an increased risk of postoperative respiratory failure in cases with lung cancer. 24
Figure 5 Example images on the median sagittal plane for the left upper lung field for three intermittent time frames in a COPD patient. Median sagittal images for the upper lung field at three intermittent time frames in an 83-year-old male patient with COPD demonstrate smaller movements in the non-dependent pleural aspect compared with the dependent pleural aspect.
…”
Section: Discussionmentioning
confidence: 99%
“…Early implementation of anatomic pneumonectomy is crucial for enhancing the survival rate of patients. Therefore, surgeons should actively participate in the assessment and functional evaluation of the patient's clinical stage and resectability, as well as determine surgical indications and techniques based on tumour progression and the patient's functional status 12 . For patients with late‐stage HAL or unresectable tumour, chemoradiotherapy can be combined with other adjuvant therapy 13 .…”
Section: Discussionmentioning
confidence: 99%
“… 40 , 41 The patients with respiratory failure post-surgery were excluded to ensure follow-up antitumor therapy. 42 The thoracic surgeons encouraged patients to perform the early rehabilitation exercises and nutritional support. Sequentially, patients received adjuvant chemotherapy or chemoradiotherapy after surgery.…”
Section: Methodsmentioning
confidence: 99%